The Development of School Culture in Building Positive Student Character : A Case Study at MTs Al-Baqiyatush Shalihat Kuala Tungkal - Mursyida, Dian; Kusnadi, Edy; Suprihatin; Rahman Fitra, Tasnim (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2024)
The phenomenon of moral degradation among the younger generation indicates the urgency of systematic interventions to prevent the decline in the quality of the nation's future leaders. In a strategic effort to address this issue, this research focuses on exploring the development of school culture at MTs Al-Baqiyatush Shalihat as an alternative model for fostering positive character. The study employs a qualitative approach with a case study design, conducted through comprehensive data collection methods, including field observations, in-depth interviews, and documentation.The research emphasizes the implementation of fundamental values encompassing religious, social, knowledge, and technological systems as the foundation for character building. The findings reveal significant success in instilling superior character traits in students, reflected in improvements in honesty, tolerance, discipline, and social responsibility. However, the study also identifies several complex challenges, including the diversity of students' backgrounds, the acceleration of information technology, and the lack of parental involvement in the character-building process.These findings underscore the need for a collaborative approach between educational institutions, families, and communities to create a conducive ecosystem for shaping a quality generation. The significance of this study lies in its contribution to designing a holistic educational intervention model that not only transfers knowledge but also actively fosters positive character in young people as a preventive measure against deviant behaviors in the future